Passiflora mucronata leaves extracts obtained from different methodologies: a phytochemical study based on cytotoxic and apoptosis activities of triterpenes and phytosterols constituents (Brazilian Journal of Pharmaceutical Sciences, 2020)
Cancer is one of the most prevalent diseases worldwide and the natural products could be a source of bioactive compounds. Passiflora mucronata (PM) belongs to a very known vegetal genus, although, there are no studies about cytotoxic activity or isolated compounds. Different extracts from PM were obtained by liquid-liquid partition (P), Soxhlet (Sox) and supercritical fluid (SFE1-5) extraction techniques, being compared concerning their yields, chemical profile and cytotoxicity. The Sox extracts showed the highest yields (6.03%: hexane; 2.51%: dichloromethane) followed by SFE (from 4.34 to 1.63%) and partitions (1.06 and 2.26%). The hexane partition (HP) showed the best cytotoxic activity against K562 cell line (IC50 = 18.72 µg.mL-1). From HP, the following compounds were identified and analysed its cytotoxic activities: β-amyrin (IC50 = 3.92 µg.mL-1), β-sitosterol (IC50 = 3.37 µg.mL-1), stigmasterol (IC50 = 3.31 µg.mL-1) and oleanolic acid. Stigmasterol induced about 75% of K562 total apoptosis. The compounds were tested against MA-104 cell line and the selective index (SI) attributed (SI >10 for all compounds). This indicates good selectivity to K562 cell line at the expense of MA-104. This is the first time, identifying those compounds to PM.